2020
DOI: 10.1002/app.49757
|View full text |Cite
|
Sign up to set email alerts
|

Studies of composite films of polyethylene oxide doped with potassium hexachloroplatinate

Abstract: The permittivity and conductivity relaxation processes of polyethylene oxide (PEO) composite along with potassium hexachloroplatinate (K 2 PtCl 6) electrolytes additive forming PEO/K 2 PtCl 6 complex composite have been investigated. The complex composite has been used as a model for dry-polymer electrolytes (PEs) due to the fact that, the anion is large enough for mimicking the immobilized anion in real dry-polymer electrolytes. Stand-free composite films with 0%, 1%, 3%, and 5% concentrations of K 2 PtCl 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The whole complex, the conductivity rises with the rise of temperature and this can be updated by the free volume model. The arc of the plots shows that ionic conductivity appears to follow Vogel–Tammann–Fulcher relation, 35 which designates that transport of ions in polymer matrices requires polymer zig‐zag motion. Miyamoto et al 36 conveyed that the ionic conductivity improved with growing temperature as a consequence of the free volume model where, the temperature rises, the polymer electrolyte is enlarged simply and harvest free volume.…”
Section: Resultsmentioning
confidence: 98%
“…The whole complex, the conductivity rises with the rise of temperature and this can be updated by the free volume model. The arc of the plots shows that ionic conductivity appears to follow Vogel–Tammann–Fulcher relation, 35 which designates that transport of ions in polymer matrices requires polymer zig‐zag motion. Miyamoto et al 36 conveyed that the ionic conductivity improved with growing temperature as a consequence of the free volume model where, the temperature rises, the polymer electrolyte is enlarged simply and harvest free volume.…”
Section: Resultsmentioning
confidence: 98%
“…The ion conduction in PEO/KOTf composite films predominantly occurs within the amorphous phase through the segmental motion of the cations (K + ) along the chains of PEO. 53 Ionic-electronic coupling in materials occurs through various mechanisms, such as electrostatic interactions, van der Waals forces, hydrogen bonding, and other intermolecular interactions. These interactions facilitate the simultaneous transport of ions and electrons within the material.…”
Section: Resultsmentioning
confidence: 99%
“…The perfect fit indicated that the system is thermally activated. This behavior can be directly related to the significant surge of the cations’ value, leading to the cation jump to the next coordinating site and, thus, increasing the energy of segment vibrations [ 46 ] which, in turn, leads to abrupt segmental motion counter to the hydrostatic pressure [ 47 ]. In addition, increasing the temperature enhances a significant carrier concentration mobility of the free electrons [ 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%